2013
DOI: 10.1016/j.jchf.2012.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Servo-Ventilation in Cardiac Function and Neurohormonal Status in Patients With Heart Failure and Central Sleep Apnea Nonresponsive to Continuous Positive Airway Pressure

Abstract: Patients with HF and unsuppressed CSA despite receiving CPAP may receive additional benefit by having CPAP replaced with ASV. Additionally, effective suppression of CSA may improve cardiac function in HF patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
41
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 18 publications
2
41
0
2
Order By: Relevance
“…Randomized and observational studies in which the effects of ASV on cardiac function were assessed showed that suppression of CSA via ASV reduced the levels of neurohumoral factors and improved LV systolic function and outcomes in chronic HF patients with CSA [106][107][108][109] . Furthermore, in studies on the effects of ASV on suppression of AHI and improvements of cardiac function in CPAP non-responders, CSA was sufficiently decreased in response to ASV, and cardiac functions and neurohumoral state were improved at 3 mo [110] . The effects of ASV on long-term clinical outcomes in chronic HF patients with CSA will be clarified in an ongoing large-scale randomized controlled trial [111,112] .…”
Section: Acute Decompensated Hfmentioning
confidence: 98%
“…Randomized and observational studies in which the effects of ASV on cardiac function were assessed showed that suppression of CSA via ASV reduced the levels of neurohumoral factors and improved LV systolic function and outcomes in chronic HF patients with CSA [106][107][108][109] . Furthermore, in studies on the effects of ASV on suppression of AHI and improvements of cardiac function in CPAP non-responders, CSA was sufficiently decreased in response to ASV, and cardiac functions and neurohumoral state were improved at 3 mo [110] . The effects of ASV on long-term clinical outcomes in chronic HF patients with CSA will be clarified in an ongoing large-scale randomized controlled trial [111,112] .…”
Section: Acute Decompensated Hfmentioning
confidence: 98%
“…69 In a second cohort of Japanese men with HFrEF whose CSA was refractory to CPAP, 3 months' treatment with peak-flow ASV delivered by nasal mask effectively suppressed central apneas, reduced urinary NE excretion and increased LVEF. 70 Thus, the innovation of ASV resolved the issue of efficacy and invigorated enthusiaccepted CPAP treatment (P=0.07 vs. untreated OSA). 45 Kasai et al documented a similar benefit but noted that a reduction in risk of death or hospitalization required good adherence to CPAP therapy.…”
Section: Randomized Trials With Mortality and Morbidity Endpointsmentioning
confidence: 99%
“…9,10) Recently, several authors reported the efficacy of ASV in improving clinical outcomes during a short-(~days) or midterm (~months) study period in patients with mild to moderate HF (New York Heart Association [NYHA] class II-III) complicated by SDB. [11][12][13][14][15][16][17][18][19][20][21][22][23][24] However, the long-term efficacy of ASV therapy in patients with advanced HF is uncertain. Moreover, most of the previous studies demonstrated improvement only in surrogate markers but not hard endpoints.…”
mentioning
confidence: 99%